2009
DOI: 10.1002/fam.997
|View full text |Cite
|
Sign up to set email alerts
|

Forensic evaluation of clothing flammability

Abstract: SUMMARYA set of 17 commercial garments were purchased, categorized based on their fabric composition and fire tested. Three fire exposures were used: (a) a simile of the United States regulatory test for apparel fabrics (16CFR1610), (b) a small vertical candle on a small swatch of fabric and (c) a candle applied to a full garment, placed on a mannequin. Comparisons were made between the results of the various tests and of the various fabrics tested. A general correlation was observed whereby increased fabric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…On the other hand, fires resulting from upholstered furniture, floor coverings, curtains, and drapes are more frequent, but result in a significantly lower rate of fatalities. The flame spread rate observed after ignition of cellulosic, common synthetics and blended fabric apparels is heavily dependent on fabric areal density, with the highest danger with lightweight fabric as shown by Hirschler et al [11,12]. Apart from low areal weight fabrics, raised-surface (highly brushed) apparel is also of concern from the point of view of high flammability hazard, because of easy ignition and fast flame spread.…”
Section: Flammability Of Textiles (General Comments)mentioning
confidence: 99%
“…On the other hand, fires resulting from upholstered furniture, floor coverings, curtains, and drapes are more frequent, but result in a significantly lower rate of fatalities. The flame spread rate observed after ignition of cellulosic, common synthetics and blended fabric apparels is heavily dependent on fabric areal density, with the highest danger with lightweight fabric as shown by Hirschler et al [11,12]. Apart from low areal weight fabrics, raised-surface (highly brushed) apparel is also of concern from the point of view of high flammability hazard, because of easy ignition and fast flame spread.…”
Section: Flammability Of Textiles (General Comments)mentioning
confidence: 99%
“…It has also been unable to address the fire risk associated with garments for the two types of populations most likely to be affected by fire: the very young and the elderly. A recent investigation of the effectiveness of the 16 CFR 1610 test and of its implications discusses the test in detail [5]. When considering apparel, it must be borne in mind that textile fabrics can be, broadly, classified into: charring and melting.…”
Section: Introductionmentioning
confidence: 99%
“…It shows that flame spread behaviors among different materials are also affected by many factors. For example, Hirschler et al (Hirschler, Zicherman, and Umino 2009) studied the flame propagation of a series of cellulose fibre fabrics and blended fabrics, and showed that the fire behavior was more dependent on the area density of fabrics than the chemical composites.…”
Section: Introductionmentioning
confidence: 99%